Experience in the application of laparoscopic appendectomy in acute appendicitis - S. N. Zavgorodniy; А. І. Rylov; М. А. Kubrak; М. В. Danyluk; O. D. Naydenov; G. M. Grishchenko (Zaporozhye State Medical University, 2016)
Laparoscopic appendectomy is the gold standard in the treatment of patients with acute appendicitis. The purpose of the study. To evaluate the results of patients who underwent laparoscopic appendectomy with the application of the clipping method for appendicular stump with titanium clips. Materials and methods. Analysis of 569 case histories of patients admitted to the 1st surgical department of Zaporozhye City Clinical Hospital of Urgent and Emergency Care with the diagnosis of "acute appendicitis" in the period from 2013 to 2015, who underwent laparoscopic appendectomy. Results. 190 patients (33.4 %) had catarrhal form of acute appendicitis, 341 patients (59.9 %) revealed phlegmonous form of inflammation of the appendix, and 38 operated patients (6.7 %) had gangrenous form. Uncomplicated forms of acute appendicitis were observed in 312 hospitalized patients (54.8 %). Complicated forms of acute inflammation of the appendix were observed in 231 patients (40.6 %). Destructive gangrenous-perforated appendicitis was detected in 26 patients (4.6 %). All patients underwent videolaparoscopy. In 7 cases (1.2 %) the conversion was performed by means of lower midline laparotomy. In the postoperative period 11 patients (1.9 %) had complications related to surgery. The average time of surgical intervention of performing laparoscopic appendectomy was 31±19 min, p<0.05. The average time in the hospital after laparoscopic appendectomy was 6.3±1.2 days, p<0.01. Conclusions. Laparoscopic appendectomy should be the gold standard in the treatment of patients with the uncomplicated forms of acute appendicitis. If suspecting a complicated form of acute appendicitis or destructive changes of the appendix the first stage of the operation should be videolaparoscopy. If unable to perform the necessary volume of surgical intervention with videolaparoscopy, one must carry out the conversion by lower midline laparotomy. Treatment of the appendicular stump by using titanium clips is not inferior in terms of reliability and safety to other methods.